Innovative mobile and Internet services in ubiquitous computing : proceedings of the 12th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS-2018) /: proceedings of the 12th International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing (IMIS-2018). ([2019]) - Unknown
No abstract available